2021
DOI: 10.1021/acs.analchem.0c05060
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Dual-Layered Metal–Organic Framework Nanostructure for Enhancing the Cell Imaging of Molecular Beacons

Abstract: As the most popular nucleic acid probe, molecular beacons (MBs) can selectively light up endogenous RNA targets without specific treatment. However, the poor cell permeability and unsatisfied intracellular stability of MBs significantly restricted their detection performance. Herein, we report the encapsulation of MB within a dual-layered metal–organic framework nanostructure UiO66-ZIF8 for enhanced cell imaging. UiO66-NH2 nanoparticles were synthesized as the template for MB loading, and the ZIF-8 shell was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Recently, metal–organic frameworks (MOF NPs) have attracted great attention in selective catalysis, gas storage and separation, and drug delivery owing to their large surface area, high and tunable porosity, and good functionalization . In particular, zeolitic imidazolate framework-8 nanoparticles (ZIF-8 NPs), a subclass of MOF NPs, have been utilized as a smart nanocarrier for accommodating functional nucleic acids containing siRNA, CpG, and DNAzyme by electrostatic interactions. Moreover, the nanoscale ZIF-8 NPs can be delivered into cells via the endocytosis pathway and then decomposed under acidic conditions of endo-lysosomes to motivate the controlled cargo release. Recent studies have found that Cu 2+ -doped ZIF-8 NPs (Cu/ZIF-8 NPs) not only maintain the unique properties of ZIF-8 NPs but also supplement an adequate amount of DNAzyme cofactor to implement the biocatalytic operation of the Cu 2+ -dependent DNAzyme in living cells. , Thus, the Cu/ZIF-8 NP-based nanoplatform could be employed as a versatile self-driven nanocarrier for the efficient delivery of DNAzyme logic circuits into cells.…”
mentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOF NPs) have attracted great attention in selective catalysis, gas storage and separation, and drug delivery owing to their large surface area, high and tunable porosity, and good functionalization . In particular, zeolitic imidazolate framework-8 nanoparticles (ZIF-8 NPs), a subclass of MOF NPs, have been utilized as a smart nanocarrier for accommodating functional nucleic acids containing siRNA, CpG, and DNAzyme by electrostatic interactions. Moreover, the nanoscale ZIF-8 NPs can be delivered into cells via the endocytosis pathway and then decomposed under acidic conditions of endo-lysosomes to motivate the controlled cargo release. Recent studies have found that Cu 2+ -doped ZIF-8 NPs (Cu/ZIF-8 NPs) not only maintain the unique properties of ZIF-8 NPs but also supplement an adequate amount of DNAzyme cofactor to implement the biocatalytic operation of the Cu 2+ -dependent DNAzyme in living cells. , Thus, the Cu/ZIF-8 NP-based nanoplatform could be employed as a versatile self-driven nanocarrier for the efficient delivery of DNAzyme logic circuits into cells.…”
mentioning
confidence: 99%
“…SNAPs are novel nucleic acid structures employing nanoparticles as cores and dense nucleic acid as shells. These nanostructures possess enhanced stability and better diagnostic and therapeutic performance. , For instance, compared with free nucleic acid molecules, the enzyme resistance effect of SNAPs is stronger. , SNAPs possess better cellular uptake effects, enabling efficient intracellular biomarker detection and drug delivery without the employment of transfection agents. Therefore, a great number of counterparts based on diverse nanoparticles have been devised. Similar to metal–organic frameworks, COFs possess many attractive structural and functional characteristics, COF-based SNAPs may be a new category of nanomaterials for theranostic applications. However, it is challenging to directly graft dense nucleic acid molecules onto COF NPs because not only there are limited connecting sites on COFs for the immobilization of the nucleic acid molecules but also the strong interaction between COF NPs and nucleic acid skeletons results in the random adsorption of these molecules onto COF NPs, making it hard to decorate the high density of nucleic acid molecules with the desired spatial arrangement to form SNAPs.…”
Section: Resultsmentioning
confidence: 99%
“…6a) [80]. In the case of delivering molecular beacons via Zr-based MOFs, selectively lighting up endogenous RNA targets have been shown by double-layer MOFs even without specific treatments [81]. Similarly, Liu et al investigated VEGF mRNA by monitoring MOFs under hypoxia in living cells.…”
Section: Efforts To Improve Delivery Efficiencymentioning
confidence: 99%